Type-II Lepra Reaction and Granulomatous Uveitis – An Unusual Presentation - Sujit Das; B. Pradeep; Pushpanjali Ojha (Delhi Journal of Ophthalmology)
We describe a case of young male who presented with lepra reaction with multiple macula-papular rash over face, forehead, ear lobules with peripheral neuropathy (Ulnar nerve thickening) and bilateral granulomatous uveitis. Slit skin smear was negative but skin nodular biopsy showed multiple discreet deeper dermis noncaseating well formed epitheloid cell granulomas with multinucleated giant cells intermixed with lymphocytes. Fite Faraco stain was negative suggestive of lepra reaction. Patient responded well with topical steroid and cycloplegic drops with disappearance of iris nodules. Systemic steroid was given for 12 weeks with gradual tapering to control lepra reaction and to prevent further ocular morbidity. Since ocular involvement can be seen even after completion of anti-leprosy treatment, the need for screening and periodic eye examination of the patient should be emphasized, for early identification of potentially sight-threatening lesions which can be easily treated. An ophthalmologist and a trained leprologist should preferably be included in the treatment of Hansen disease with ocular manifestations.